Decoding plasma cell maturation dynamics with BCMA - Schulz, Sebastian; Menzel, Shannon; Wittner, Jens; Ulbricht, Carolin; Grofe, Alina T.; Roth, Edith; Mann-Nüttel, Ritu; Scheu, Stefanie; Kueh, Andrew J.; Jäck, Alexander; Herold, Marco J.; Hauser, Anja E.; et al. (Frontiers in Immunology, 2025)
Plasma cells provide protective antibodies following an infection or vaccination. A network of intrinsic and extrinsic factors fine-tunes the generation of a heterogenous plasma cell pool with varying metabolic requirements, transcriptional profiles and lifespans. Among these, the B cell maturation antigen (BCMA) has been implicated in the APRIL-mediated survival of long-lived plasma cells. To characterize the terminal maturation of plasma cells, we constructed a BCMA reporter mouse (BCMA:Tom) that exclusively labeled antibody-secreting cells and revealed that BCMA:Tom expression varied by IgH isotype and increased with plasma cell maturity. The BCMA reporter, used alongside the Blimp1-GFP reporter, also allowed detailed tracking of plasma cell development and highlighted the importance of the in vivo microenvironment to complete plasma cell maturation. Therefore, the BCMA:Tom reporter mouse provides a valuable tool for tracking plasma cell development and maturation with flow cytometry or advanced imaging techniques, enabling a deeper understanding of the mechanisms regulating plasma cell heterogeneity and longevity.
CRIS-Team Scopus Importer:2025-04-01
Keywords: antibody-secreting cells (ASC); BCMA (TNFRSF17); bone marrow; plasma cells; spleen; survival; thymus

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

The microRNA processing subunit DGCR8 is required for a T cell-dependent germinal center response - Daum, Patrick; Ottmann, Shannon; Meinzinger, Julia; Schulz, Sebastian; Corte-Real, Joana; Hauke, Manuela; Roth, Edith; Schuh, Wolfgang; Mielenz, Dirk; Jäck, Hans-Martin; Pracht, Katharina (Frontiers in Immunology, 2022)
We have previously shown that the microRNA (miRNA) processor complex consisting of the RNAse Drosha and the DiGeorge Critical Region (DGCR) 8 protein is essential for B cell maturation. To determine whether miRNA processing is required to initiate T cell-mediated antibody responses, we deleted DGCR8 in maturing B2 cells by crossing a mouse with loxP-flanked DGCR8 alleles with a CD23-Cre mouse. As expected, non-immunized mice showed reduced numbers of mature B2 cells and IgG-secreting cells and diminished serum IgG titers. In accordance, germinal centers and antigen-specific IgG-secreting cells were absent in mice immunized with T-dependent antigens. Therefore, DGCR8 is required to mount an efficient T-dependent antibody response. However, DGCR8 deletion in B1 cells was incomplete, resulting in unaltered B1 cell numbers and normal IgM and IgA titers in DGCR8-knock-out mice. Therefore, this mouse model could be used to analyze B1 responses in the absence of functional B2 cells.
CRIS-Team WoS Importer:2023-01-27